Internationalization of the construction industry in the global value chain - Niu, Wentao; Xu, Zhenzhen; Liu, Bin; Liu, Chunlu (Technological and Economic Development of Economy, 2023)
The construction sector plays a significant role in national economic development and accounts for a dominant portion of national economic growth. The international construction industry’s development has been explored from the perspective of the economy. Internationalization improves awareness about participation in international trade activities. This paper aims to quantify the internationalization of the construction industry in the global value chain. The sectoral participation index and interaction index are conducted to evaluate the internationalized degree of the construction industries. In the results, the distribution of the backward participation indices shows nearly all countries’ internationalization processes were still at the stage of benefiting from primary resources. The forward support index is easily influenced by the scale effect. The backward independence index accounts for a small percentage of national imports measured by value added. The main source of value-added supply was the local construction sector. This study proposes a comprehensive indicator to quantify the internationalization of the construction industries in the sight of national and global points. The references have a positive value for policymakers in the management of value-added flows in the international market and adjustment of the foreign trade environment.